Short-Term Performance of IPO Stocks on the Indonesia Stock Exchange: Do Firm Sizes Matter? - Samudra, Suryadi (IJESS International Journal of Education and Social Science, 2025)
This study examines the short-term performance of Initial Public Offering (IPO) stocks on the Indonesia Stock Exchange (IDX) by analyzing the role of firm size. A total of 60 IPO-listed companies between 2021 and 2024 were categorized into three groups—small, medium, and large—based on total assets at the time of listing. Using abnormal return as the performance metric, the study evaluates daily and cumulative returns over a 45-day period post-IPO. Findings reveal that small firms tend to experience higher abnormal returns on the first day of trading, consistent with the underpricing phenomenon often attributed to higher information asymmetry and investor speculation. However, in the longer short-term window, large firms accumulate significantly greater cumulative abnormal returns, reflecting stronger investor confidence and market stability. The Kruskal-Wallis test confirms a statistically significant difference in abnormal returns between small and large firms. These results indicate that firm size influences investor perception and post-listing price behavior. While smaller firms benefit from short-term speculative gains, larger firms offer more sustained performance. The study underscores the need for investors and regulators to account for firm size when evaluating IPO opportunities in emerging markets.